The influence of message persuasiveness on the eWOM trustworthiness of the purchase behavior of search products - Malik, Samra; Rizwan, Muhammad (The journal of contemporary issues in business and government, 2021)
Purpose: Over the time, consumption of online social platforms in order to share word of mouth about clothing has increased. However, the mechanism by which message persuasiveness influenced through eWOM on purchase of clothing has yet to be fully understood. This study develops a research framework that focuses on the influence of message persuasiveness on the eWOM trustworthiness of the search products’ purchase behavior. Design/Methodology/Approach: This study collected data from a sample of 258 respondents using online questionnaires. Confirmatory factor analysis was performed to investigate the influence. Findings: The results show the significant positive influence of Message Persuasiveness (MP) on the eWOM Trustworthiness (ETW) and the eWOM Trustworthiness on the intentions to buy Search products (SP). The study confirms that eWOM Trustworthiness mediates the relationship between Message Persuasiveness and intentions to buy Search products. Implications/Originality/Value: This empirical study can enable managers to better understand the effects of eWOM Trustworthiness on intentions to buy Search products. Our results should encourage marketers to work with SNSs to develop viral marketing campaigns, encouraging customers to spread useful and credible eWOM trustworthiness to improve purchase intentions.